Sharing Poetry in the Health and Wellness Coaching Engagement: A Phenomenological Study - Elizabeth Ahmann; Micah Saviet; Marybeth Missenda (International Journal of Evidence Based Coaching and Mentoring)
Poetry can tap into feelings, stimulate creativity, and prompt inspiration and insight. Some coaches have reported these benefits when sharing poetry with clients, but little research has explored the use of poetry in the coaching engagement. This retrospective phenomenological study explored perceptions of poetry as a tool for health and wellness coaching among 40 coaches enrolled in an online advanced coaching skills class. Six overarching themes–discernment, logistics, impact on coaching, effect on the client, mechanisms, and the coach’s personal experience–are illustrated using verbatim quotations. This study may prompt coaches and researchers to explore novel approaches, including poetry, for broadening the toolboxes and eliciting enhanced client insight and awareness.